2014
DOI: 10.1109/tits.2014.2312315
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic Aircraft Trajectory Optimization

Abstract: North Atlantic oceanic airspace accommodates air traffic between North America and Europe. Radar-based surveillance is not applicable in this vast and highly congested airspace. For conflict-free flight progress, the Organized Track System is established in North Atlantic, and flights are prescribed to follow pre-defined oceanic tracks. Rerouting of aircraft from one track to another is very rarely applied because of large separation standards. As a result, aircraft often follow routes that are not optimal in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…The same authors applied the Genetic Algorithm (GA) to resolve a similar optimization problem in [10] for the real flight data involving about 350 flights. Simulations showed that a conflict-free solution can be found only under the reduced separation norms which revealed benefits from operating the ADS-B.…”
Section: Related Workmentioning
confidence: 99%
“…The same authors applied the Genetic Algorithm (GA) to resolve a similar optimization problem in [10] for the real flight data involving about 350 flights. Simulations showed that a conflict-free solution can be found only under the reduced separation norms which revealed benefits from operating the ADS-B.…”
Section: Related Workmentioning
confidence: 99%
“…A number of contributions also come from the related problem of conflict-free trajectory planning (i.e., finding trajectories such that aircraft are separated all along their path, a priori in long-term strategical planning or in tactical phases of flights). In [9,23] mixed-integer models are proposed for trajectory planning problems, that are solved through heuristic approaches. Interesting MINLP problems also come from mixed-integer optimal control models for conflict-free trajectories planning and conflicts resolution, where typical discretization steps lead to the solution of MINLP problems, see e.g.…”
Section: Aircraft Conflict Avoidancementioning
confidence: 99%
“…Alternatively, some authors resort to heuristics [4,9,23], and are able to solve large instances, though obtaining feasible (if any) but not guaranteed global optimal solutions. More specifically, a Variable Neighborhood Search metaheuristic is proposed in [4], while a simulated annealing and, respectively, a genetic algorithm tailored to the problem are used in [9,23] for the related problem of trajectory planning. Finally, in [8], besides the exact solution of the whole MINLP, a heuristic is proposed, based on exact solutions of subproblems that are represented by clusters of conflicting aircraft.…”
Section: Solution Approachesmentioning
confidence: 99%
“…This change can be a re-routing from the initial track, switching to another flight level or varying the Mach number. In [5], authors assumed that all aircraft are equipped with ADS-B systems. Thus, the reduced separation standards can be applied.…”
Section: B Ads-b Systemsmentioning
confidence: 99%